High Strength, Strain, and Resilience of Gold Nanoparticle Reinforced Eutectogels for Multifunctional Sensors - Yingxiang Huang; Yanzhao Yang; Cong Peng; Yu Li; Wei Feng (Advanced Science)
Abstract Eutectogels with inherent ionic conductivity, mechanical flexibility, environment resistance, and cost‐effectiveness have garnered considerable attention for the development of wearable devices. However, existing eutectogels rarely achieve a balance between strength, strain, and resilience, which are critical indicators of reliability in flexible electronics. Herein, poly(sodium styrenesulfonate) (PSS)‐modified gold nanoparticles (AuNPs) in eutectic solvents are synthesized, and PSS‐AuNP reinforced polyacrylic acid/polyvinylpyrrolidone (SAu‐PAA/PVP) eutectogel is successfully prepared. Through the coordination between AuNPs and the PAA/PVP polymer chains, the SAu‐PAA/PVP eutectogel exhibits significantly enhanced tensile strain (946%), mechanical strength (3.50 MPa), and resilience (85.3%). The high‐performance eutectogel was demonstrated as a flexible sensor sensitive to strain and temperature, and the AuNPs provided near‐infrared sensing capabilities. Furthermore, SAu‐PAA/PVP eutectogel inherits the benefits of ES, including anti‐drying and anti‐freezing properties (−77 °C). Moreover, the eutectogel is microstructured using a simple molding method, and the resulting hierarchical pyramid microstructured eutectogel functions as ionic dielectric layer in a pressure sensor. This sensor exhibits high sensitivity (37.11 kPa−1), low detection limit (1 Pa), a fast response rate (36/54 ms), and excellent reproducibility over 5000 cycles, making them reliable and durable for detecting small vibrations, with potential applications in precision machinery, aerospace, and buildings.